ROLES FOR ADVANCED PRACTICE NURSES: CREATION, APPLICATION, AND ASSESSMENT ROLES IN ADVANCED PRACTICE NURSING: - Mariam Shaker Aljasser, ‏Ahlam Muteb Almutairi, ‏Taghreed Saleh Bin Jawir, ‏Rania Hassen Alallawi, ‏Haifa Mohammad Hawswai, ‏Ashwaq Abdrhman Alzid (Chelonian Research Foundation, 2022)
formulation, application, and assessment Objective. The six issues that influenced the introduction of advanced practice nursing (APN) roles are discussed in this paper: the lack of clarity surrounding the terminology used in APN, the underutilization of all APN role domains, the role's emphasis on physician replacement/support, the failure to address environmental factors that undermine the roles, and the limited application of evidence-based approaches to inform development, implementation, and evaluation. Context. The number and variety of APN positions have significantly increased as a result of health care reorganization in various nations. It's frequently unclear how much of advanced nursing practice these professions actually reflect. Realizing the full potential and impact of APN positions on health is hampered by incorrect conceptions of their purpose, inconsistent titling and educational preparation, and misuse of APN terminology. Problems with role overload, role conflict, and inconsistent stakeholder acceptability are commonly mentioned while discussing the implementation of APN roles. Keywords: role barriers, role implementation, role evaluation, advanced nursing practice, and nursing